Signal transduction during C. elegans vulval development: a NeverEnding story. (June 2015) - Schmid, Tobias; Hajnal, Alex
Abstract : The Caenorhabditis elegans hermaphrodite vulva is one of the best studied models for signal transduction and cell fate determination during organogenesis. Systematic forward genetic screens have identified a complex and highly interconnected signaling network formed by the conserved EGFR, NOTCH, and WNT signaling pathways that specifies an invariant pattern of cell fates among the six vulval precursor cells (VPCs). Multiple inhibitory interactions between the EGFR and NOTCH pathways ensure the selection of a single 1° VPC that is always flanked by two 2° VPCs thanks to lateral NOTCH signaling. Building on this 'central dogma' of cell fate specification, scientists have investigated a broad spectrum of novel questions that are summarized in this review. For example, vulval development is a unique model to study the intracellular trafficking of signaling molecules, such as NOTCH or EGFR, to investigate the interactions between the cell cycle and cell fate specification pathways, and to observe epithelial tube morphogenesis and cell invasion at single-cell resolution. Finally, computer scientists have integrated the experimental data into mathematical and state-based ' in silico ' models of vulval development, allowing them to test the completeness and limits of our current understanding.